Phytoremediation potentials of eight plant species on the tropical gold mine reclamation site in North Sumatra, Indonesia - SYAIFUL ANWAR; ASYRAF BIN MANSOR; HAZZEMAN HARIS; QESHY NATA HAYATI; NIR FATHIYA; BUDIMAN BUDIMAN (Smujo International, 2026)
Abstract. Anwar S, Mansor AB, Haris H, Hayati QN, Fathiya N, Budiman. 2026. Phytoremediation potentials of eight plant species on the tropical gold mine reclamation site in North Sumatra, Indonesia. Asian J Agric 10 (1): g100148. https://doi.org/10.13057/asianjagric/g100148. Post-mining landscapes are often characterized by degraded soils and elevated concentrations of metals, which may hinder ecological recovery and vegetation establishment. This study assessed the accumulation and translocation of metals, i.e., ferrum (Fe), manganese (Mn), zinc (Zn), copper (Cu), nickel (Ni), and aluminium (Al), in eight fast-growing plant species (i.e., Falcataria falcata, Hibiscus tiliaceus, Ixonanthes reticulata, Macaranga conifera, Macaranga tanarius, Melaleuca cajuputi, Melastoma malabathricum, and Samanea saman) at the Martabe gold mining reclamation site, North Sumatra, Indonesia. Soil and plant samples were collected from three reclaimed areas and analyzed using Atomic Absorption Spectrophotometry (AAS). Phytoremediation potentials were assessed using bioconcentration factors (BCF), translocation factors (TF), and phytomining potentials. The results showed that reclaimed soils were acidic and characterized by very high Al concentration (mean 110,100 mg kg-¹) and Fe concentrations (mean 83,309 mg kg-¹) and moderate concentrations of Mn (mean 653 mg kg-¹), Zn (mean 410 mg kg-¹), Cu (mean 277 mg kg-¹), and Ni (mean 513 mg kg-¹). Five planted species showed medium Mn accumulation (BCF 0.1-1), low Zn accumulation in all planted species (BCF 0.01-0.1) and low and negligible uptake in eight species of Fe, Cu, Ni, and Al. Translocation factors indicated Zn and Cu were preferentially translocated to shoots (TF>1), supporting phytoextraction, while Mn exhibited mixed translocation, with M. conifera acting as a phytostabilizer. Leguminous species, particularly I. reticulata, M. cajuputi, and S. saman, demonstrated relatively higher root-to-shoot translocation efficiencies. Preliminary phytomining estimates, based on single-plot biomass measurements, indicated a greater potential removal for Al (up to 13.7 kg ha-¹), Mn (up to 5.1 kg ha-¹), and Fe (up to 3.15 kg ha-¹) compared to other metals. The results demonstrate clear functional differentiation among planted species, and highlight the importance of trait-based species selection and mixed-species plantings to optimize phytoremediation and support revegetation on reclaimed gold mining lands.